STUDY OF THE STRONG-COUPLING CONSTANT USING W-PLUS JET PROCESSES - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1995)
The ratio of the number of W+1 jet to W+0 jet events is measured with the D0 detector using data from the 1992-93 Tevatron Collider run. For the W→eν channel with a minimum jet ET cutoff of 25 GeV, the experimental ratio is 0.065±0.003stat±0.007syst. Next-to-leading order QCD predictions for various parton distributions agree well with each other and are all over 1 standard deviation below the measurement. Varying the strong coupling constant αs in both the parton distributions and the partonic cross sections simultaneously does not remove this discrepancy. © 1995 The American Physical Society.